1976
DOI: 10.1111/j.1570-7458.1976.tb02645.x
|View full text |Cite
|
Sign up to set email alerts
|

SEX PHEROMONE OF THE POTATO TUBERWORM MOTH, PHTHORIMAEA OPERCULELLA: ISOLATION, IDENTIFICATION AND FIELD EVALUATION

Abstract: The sex pheromone of the potato tuberworm moth, Phthorimaea operculella (Zell.) has been identified as a mixture of trans‐4, cis‐7‐tridecadienyl acetate and trans‐4, cis‐1, cis‐10 tridecatrienyl acetate. The identifications have been carried out by means of electroantennography, mass, infrared and n.m.r. spectroscopy. The identifications have been confirmed by synthesis. Both compounds occur in the insects in about equal amounts. The individual compounds are attractive to male moths in pheromone traps. The tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 15 publications
0
28
0
1
Order By: Relevance
“…56 T. Ando et al The straight chain is dominantly formed with even-numbered carbons because the Type I compounds are derived de novo via general saturated fatty acids such as palmitic acid (16:Acid) and stearic acid (18:Acid). However, exceptions do exist as pheromone components with an odd number chain have been determined from six species: E4,Z7-13:OAc and E4,Z7,Z10-13:OAc from P. operculella, [11], E4-13:OAc from the tomato pinworm (Keiferia lycopersicella, Gelechiidae) [12], E3-13:OAc from the tobacco stem borer (Scrobipalpa heliopa, Gelechiidae) [13], Z8-13:OAc and Z10-15:OAc from the sugarcane stalk borer (Chilo auricilius, Pyralidae: Crambinae) [14], E8,Z10-15:OAc and E9-15:OAc from the cranberry fruitworm (Acrobasis vaccinii, Pyralidae: Phycitinae) [15], and Z11-17:OAc from the cabbage armyworm (Mamestra brassicae, Noctuidae: Hadeninae) [16]. Figure 3A shows the location of the double-bond relative to a functional group of the Type I monoenyl components.…”
Section: Type I Compounds With a Common Functional Groupmentioning
confidence: 99%
“…56 T. Ando et al The straight chain is dominantly formed with even-numbered carbons because the Type I compounds are derived de novo via general saturated fatty acids such as palmitic acid (16:Acid) and stearic acid (18:Acid). However, exceptions do exist as pheromone components with an odd number chain have been determined from six species: E4,Z7-13:OAc and E4,Z7,Z10-13:OAc from P. operculella, [11], E4-13:OAc from the tomato pinworm (Keiferia lycopersicella, Gelechiidae) [12], E3-13:OAc from the tobacco stem borer (Scrobipalpa heliopa, Gelechiidae) [13], Z8-13:OAc and Z10-15:OAc from the sugarcane stalk borer (Chilo auricilius, Pyralidae: Crambinae) [14], E8,Z10-15:OAc and E9-15:OAc from the cranberry fruitworm (Acrobasis vaccinii, Pyralidae: Phycitinae) [15], and Z11-17:OAc from the cabbage armyworm (Mamestra brassicae, Noctuidae: Hadeninae) [16]. Figure 3A shows the location of the double-bond relative to a functional group of the Type I monoenyl components.…”
Section: Type I Compounds With a Common Functional Groupmentioning
confidence: 99%
“…Afterwards, research by Fouda et al (1975Fouda et al ( ), (1975, Roelofs et al (1975), Persoons et al (1976), Yamoaka et al (1976), Bacon et al (1976), Voerman et al (1977, Voerman and Rothschild (1978), identified, isolated, and synthesized the two main pheromone compounds, finding that combining them attracted the male moths more than each compound taken separately. Bacon et al (1976) and Raman (1982; also evaluated the most effective rates of these two compounds in the mixture preparation, as well as some techniques to use these compounds in field and storage traps.…”
Section: Introductionmentioning
confidence: 99%
“…According to Herman et al (2005), two chemicals have been identified as the main component of P. operculella sex pheromone: (E4,Z7)-tridecadienyl acetate (PTM1) (Roelofs et al 1975) and (E4,Z7,Z10)-tridecatrienyl acetate (PTM2) (Persoons et al 1976); both chemicals were synthesized, blended, and tested (Voerman and Rothschild 1978;Raman 1988). Since some other insects, including other Gelechiidae moths could be trapped in the sticky liners, they should be changed once a week for easy viewing of adult moths; lures should be changed monthly but may be used longer, depending on environmental conditions; at cooler temperatures the longevity of the lures increases (Rondon et al 2007).…”
Section: Controlling the Potato Tuberwormmentioning
confidence: 99%